Catalytic Functionalization of Methane and Light Alkanes in Supercritical Carbon Dioxide. Issue 35 (25th July 2014) - Fuentes, M. Ángeles; Olmos, Andrea; Muñoz, Bianca K.; Jacob, Kane; González‐Núñez, M. Elena; Mello, Rossella; Asensio, Gregorio; Caballero, Ana; Etienne, Michel; Pérez, Pedro J.
Abstract The development of catalytic methods for the effective functionalization of methane yet remains a challenge. The best system known to date is the so‐called Catalytica Process based on the use of platinum catalysts to convert methane into methyl bisulfate with a TOF rate of 10−3 s. In this contribution, we report a series of silver complexes containing perfluorinated tris(indazolyl)borate ligands that catalyze the functionalization of methane into ethyl propionate upon reaction with ethyl diazoacetate (EDA) by using supercritical carbon dioxide (scCO2) as the reaction medium. The employment of this reaction medium has also allowed the functionalization of ethane, propane, butane, and isobutane.